A symbolic legislative gesture? An argument for active enforcement of the insider trading prohibition in Myanmar. Issue 1 (2nd January 2020) - Gillis, Matilda
Abstract : The object of this short article is to examine one aspect of Myanmar's recent market reform, namely, its prohibition of insider trading. The prohibition is itself uncontroversial and brings Myanmar into line with the securities laws of most other developed nations. The focus of this article is, rather, on whether the prohibition should be actively enforced or left to function as a mere symbolic legislative gesture. It is argued here that active enforcement is desirable in the developing economy context, but that the current legislative formulation of the insider trading prohibition in Myanmar leaves the prohibition to function really only as a symbolic gesture. The article undertakes a short comparative analysis with the Australian prohibition of insider trading and concludes both that prosecution under the current prohibition would be difficult and that legislative amendment is required.